2011
DOI: 10.1111/j.1466-8238.2011.00664.x
|View full text |Cite
|
Sign up to set email alerts
|

Processes at multiple scales affect richness and similarity of non‐native plant species in mountains around the world

Abstract: Aim To investigate how species richness and similarity of non-native plants varies along gradients of elevation and human disturbance.Location Eight mountain regions on four continents and two oceanic islands. MethodsWe compared the distribution of non-native plant species along roads in eight mountainous regions. Within each region, abundance of plant species was recorded at 41-84 sites along elevational gradients using 100-m 2 plots located 0, 25 and 75 m from roadsides. We used mixed-effects models to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
184
0
18

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 140 publications
(214 citation statements)
references
References 43 publications
12
184
0
18
Order By: Relevance
“…Non-native plant abundance tends to decrease away from roadsides (Arevalo et al 2010;Timmins and Williams 1989), and this pattern has been shown to be exacerbated along an elevation gradient within the GYE (Seipel et al 2012). In order to better understand the process of non-native plant invasion along roadways in the GYE, we examined the relationship of elevation and distance from road to non-native plant richness at the landscape scale.…”
Section: Introductionmentioning
confidence: 99%
“…Non-native plant abundance tends to decrease away from roadsides (Arevalo et al 2010;Timmins and Williams 1989), and this pattern has been shown to be exacerbated along an elevation gradient within the GYE (Seipel et al 2012). In order to better understand the process of non-native plant invasion along roadways in the GYE, we examined the relationship of elevation and distance from road to non-native plant richness at the landscape scale.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true for many exotics that have not yet occupied all suitable regions in their introduced range (Alexander and Edwards 2010). Whether an introduced species will successfully invade a montane ecosystem depends on a range of factors such as species plasticity, local disturbance regime, biotic and abiotic resistance, and propagule pressure McDougall et al 2011;Molina-Montenegro et al 2012;Seipel et al 2012;Van Rensburg et al 2013). The lack of adequate datasets on the distributional range of exotics, however, makes it difficult to disentangle the relative importance of each of these factors.…”
Section: Introductionmentioning
confidence: 99%
“…Esto podría explicarse debido a que ambos sitios corresponden a bordes de caminos, por lo tanto, a pesar de trabajar a escala local (donde probablemente los recursos serían más limitantes y la interacción debería ser negativa), se les está otorgando el espacio disponible para no competir por recursos (Shea & Chesson 2002). De esta manera, tanto las plantas introducidas como las nativas estarían utilizando los nichos disponibles dejados por la fragmentación del hábitat, ya que los caminos son considerados hábitats propicios particularmente para el establecimiento de especies de plantas introducidas (Trombulak & Frissell 2000, Arévalo et al 2005, Seipel et al 2012, pero para este caso, también para especies nativas dada la matriz vegetacional en la que se encuentran estos caminos.…”
Section: Discussionunclassified